Aktivitas Pasar Modal Indonesia Selama Era Pandemi dan Pasca Pandemi - Durrotunnashihatil Unsaa Dhiyaa Ulhaqqi; Siti Amamilah; Lepat Raharjo; Dwi Epty Hidayaty (Jurnal Ilmiah Wahana Pendidikan, 2023)
The multidimensional crisis due to the Covid-19 pandemic has come so quickly and exposed the fragility of a country in various fields. In the health sector, this pandemic, for example, shows how inadequate and evenly distributed health facilities are in many countries, including the United States and Italy, which were previously considered to be quite advanced in terms of public health facilities. In the economic field, the crisis caused by the Covid-19 pandemic has developed in such a way and caused a contraction in the global economy. world financial institutions estimate that the Covid-19 pandemic will cause a contraction in the world economy by -2.0% to 2.8% in 2020, from previously growing by an average of 2.9% in 2019. At the same time, the Covid-19 pandemic it is also expected to reduce global trade and investment flows by up to 30%, as well as increase world financial market volatility by up to 215%. This research will discuss the activities of the Indonesian capital market during the pandemic and post-pandemic eras. This research uses qualitative methods because this research only describes situations or events and does not look for or explain relationships and does not test hypotheses or make predictions. The results of the research show that the performance of the Indonesian Capital Market in 2021 showed stable and improving performance, which was reflected in, among other things, market stability, trading activity, the amount of fundraising and the number of retail investors which reached a record high.